Doxorubicin biocompatible O/W microemulsion stabilized by mixed surfactant containing soya phosphatidylcholine - Formariz, T. R.; Sarmento, V. H. V.; Silva-Junior, A. A.; Scarpa, M. V.; Santilli, Celso Valentim [UNESP]; Oliveira, A. G. (Elsevier B.V., 2006)
Microemulsions (ME) containing soya phosphatidylcholine (SPC/polyoxyethylenglycerol trihydroxystearate 40 (EU)/sodium oleate (SO) as surfactant cholesterol (CHO) as oil phase and aqueous buffer were studied. Pseudo-ternary phase diagrams of the investigated systems were obtained at constant SPC/EU/SO weight ratio 3.5:3.5:3.0 by titration, in order to characterize the proportions between the components to form clear systems. The dynamic light scattering results showed that the size of the oil droplets decreases significantly with the ratio of surfactant/oil phase added to system. Depending on the composition ME system could exhibit a thixotropic behavior. The apparent viscosity increased 25- and 13-folds with cholesterol concentration for drug-free and drug-load ME, respectively. It was also verified that the octanol/aqueous buffer partition coefficient (K-O/B) of doxorubicin (DOX) was pH dependent increasing abruptly above pH 6.0. It was possible to incorporate 2.24 mg/ml of DOX into ME. The incorporation of DOX in the ME systems increased the droplets size for all surfactant concentrations used in the system. The results suggest that DOX interacts with the microstructure of the ME at the studied pH increasing significantly the drug solubility. It was possible to conclude that the investigated ME can be a very promising vehicle as drug-carrier for administration of doxorubicin. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: microemulsion; soya phosphatidylcholine; drug delivery; doxorubicin